Modelling UK Mortgage Default in Light of the Financial Crisis - Wongwachara, Warapong (Henry Stewart Talks, 2010)
Review of the recent financial crisis, Evolution in the UK housing market, Modelling strategies, Drivers of mortgage default, Econometric models of mortgage default, Vector Autoregression (VAR) of default variables, VAR with macroeconomic default drivers, Threshold VAR: A non-linear relationship, Forecast competition, Conclusion: key features for successful modelling of mortgage default
Updated at 2010/11/29, Archived at 2022/04/04